Academic dishonesty and misconduct: Curbing plagiarism in the Muslim world - Moten, Abdul Rashid (IIUM Press, 2014)
Plagiarism is the theft of someone’s ideas or language, and is a form of cheating which is morally and ethically unacceptable. This study analyses the nature of plagiarism from an Islamic perspective and its prevalence in institutions of higher learning in the Muslim world, especially among faculty members. It also examines the ways in which universities attempt to minimise or marginalise plagiarism. This study is warranted by the fact that there is relatively very little research on the issue of plagiarism at universities in the Muslim world and that existing research seldom addresses the issue of academics engaged in such unethical practices. Based upon existing surveys, interviews, and documentary sources, the study found that in earlier periods, standards were not inevitably lower than those that exist today and that the scope for condemning plagiarists has always existed. It also found that despite Islam’s loathing, the incidence of plagiarism has grown significantly among Muslim students and faculty members in the Muslim world. The response to plagiarism varies from country to country. Some Muslim countries tolerate plagiarism, while others are taking steps to curb it. Institutions in Malaysia approach the problem of plagiarism as a matter of morality and crime that emphasise the need to develop writing and researching skills. They resort to honour codes, emphasise law and enforcement, and teach ways to write and cite. However, the success of these methods needs to be further probed.